Integrating Educational Philosophy into the Development of Islamic Education Practices in the Modern Era - Nurul Aini; Komarudin Sassi (CV. Creative Tugu Pena, 2025)
This study examines the integration of educational philosophy into the development of Islamic education practices in the modern era, characterized by rapid social, cultural, and technological change. Islamic education is not only oriented toward the transmission of knowledge but also toward the formation of holistic character and morality. In the face of globalization and digitalization, Islamic education must remain grounded in the core values of faith and ethics while adapting to the needs of contemporary learners. Employing a qualitative approach with a descriptive–analytical method, this study draws on literature from major educational philosophies—Perennialism, Progressivism, Constructivism, Reconstructionism, Idealism, and Realism—as well as key Islamic educational thinkers. The findings reveal that Islamic education benefits from integrating the timeless values emphasized by Perennialism and Idealism with the progressive, learner-centered, and contextual approaches of Progressivism, Constructivism, and Reconstructionism. Such integration strengthens the spiritual, intellectual, and life-skill dimensions of learners while fostering critical, creative, and adaptive dispositions in navigating societal change. Consequently, Islamic education serves a dual function: preserving its rich scholarly tradition rooted in Islamic teachings and acting as a transformative force that remains relevant, solution-oriented, and competitive in the global era.